PTU-010 A Combination of Pillcam®SB2 and Smartpill® in the Investigation of Patients Referred for Assessment of Known or Suspected Small-Bowel Crohn's Disease & Their Association with Faecal Calprotectin Levels; Case Series. (17th August 2016) - Yung, DE; Plevris, J; Koulaouzidis, A
Abstract : Introduction: SmartPill® (Given Imaging Corp., Yoqneam, Israel) is an ingestible, wireless, non-imaging capsule device that records physiological data including contractions, pH and temperature throughout the gastrointestinal (GI) tract. 1 There are currently scarce data looking at SmartPill® assessment of patients with known or suspected small-bowel Crohn's Disease(CD). 2 We designed this pilot study to investigate feasibility and safety of SmartPill® assessment of gut motility in this group (local ethics committee approval ref.12/SS/0013). Methods: Over one year (2012), patients with known or suspected CD, referred for small-bowel capsule endoscopy (SBCE), were invited to participate. Patients underwent hydrogen breath test to exclude small-bowel bacterial overgrowth, patency capsule (Agile®) to confirm luminal patency and provided stool samples for faecal calprotectin (FC). Patients ingested PillCam®SB2, then SmartPill®4 h afterwards. Thirty-three healthy controls were obtained from unpublished data. For statistical analysis, P < 0.05 was considered significant. Results: Over the aforementioned period, 12 patients were recruited (7 F/5 M, mean age 44.2 ±16.6 years). 10 underwent complete SmartPill® examination (1 stomach retention, 1 dropout). Pillcam®SB2 was complete in 10 (1 stomach retention, 1 dropout). Mean FC was 340 ±307.7 μg/g. The study group had longer transit times and lower gut motility index (MI) compared to controls, where MI = Ln (sum of pressure amplitudes × number of contractions + 1). The difference in motility appears statistically significant (P < 0.05). Transit times for SmartPill® were longer than PillCam®SB2 (not statistically significant), possibly due to differences in capsule specifications. Limitations: signal loss from SmartPill® (5/10 studies), possibly due to radiofrequency interference. Conclusion: This study is the first pilot to attempt combining SBCE and SmartPill® in clinical assessment of small-bowel CD. Current data on motility in CD is scarce. Multimodal information could provide a clearer clinical picture. 3–5 Furthermore, despite concerns about capsule retention in CD patients, our study suggests SmartPill® appears safe for use if a patency capsule is employed beforehand. References: 1 Tran K, Brun R, Kuo B. Evaluation of regional and whole gut motility using the wireless motility capsule: relevance in clinical practice. Therap Adv Gastroenterol 2012;5 :249–260. 2 Rao SSC, Camilleri M, Haler WL, et al . Evaluation of gastrointestinal transit in clinical practice: position paper of the American and European Neurogastroenterology and Motility Societies. Neurogastroenterol Motil 2011;23 :8–23. 3 Koulaouzidis A, Iakovidis DK, Karargyris A, et al . Wireless endoscopy in 2020: Will it still be a capsule? World J Gastroenterol 2015;21 :5119–30. 4 Dignass A, Van Assche G, Lindsay JO, Lémann M, Söderholm J, et al . The second European evidence-based consensus on the diagnosis and management of Crohn's disease: current management. J Crohns Colitis 2010;4 :28–62. 5 Fireman Z, Mahajna E, Broide E, Shapiro M, Fich L, et al . Diagnosing small bowel Crohn's disease with wireless capsule endoscopy. Gut 2003;52 :390–92. Disclosure of Interest: D. Yung: None Declared, J. Plevris: None Declared, A. Koulaouzidis Grant/research support from: ESGE- Given®Imaging Research grant 2011